Inventory and Monitoring of Land Degradation Processes Using Space Data - Christian, Binal A; Dhinwa, P S; Ajai, Ajai (Annals of Arid Zone, 2019)
Land degradation is one of the major environmental hazards, affecting the living conditions of millions of people all across the world. Inventory and monitoring of the land degradation status are the primary requirement in preparation of mitigation plan to combat land degradation. The present paper, therefore, aims at the creation of spatial inventory of land degradation processes using satellite data. Multi-season Landsat TM data of 30 m spatial resolution, pertaining to the years 1992, 2001 and 2016, have been analysed to prepare land degradation maps of Ballia district, Uttar Pradesh state in northern India. Monitoring and assessment of the desertification has been carried out for a period of 24 years. In this study, an attempt is made to monitor the changes in land degradation status during 1992 to 2016 by using multi-temporal satellite data. Water logging and sodicity in agricultural land are the major processes of land degradation active in Ballia district. Analysis of satellite data reveals that area under sodicity in agriculture land has increased from 23.04 km2 in 1992 to 25.08 km2 in 2016, while water logging in agricultural land has increased from 199.92 km2 in 1992 to 210.25 km2 in 2016. Key words: Land degradation, monitoring, multi-temporal, satellite data